Validity and Reliability of the Turkish St. Mark’s Incontinence Score - Ersoy, Özdal; Ecem Temel, Yasemin (Turkish Journal of Gastroenterology, 2026)
Background/Aims: The St. Mark’s Incontinence Score (SMIS) is a widely used tool for assessing anal incontinence severity. This study aimed to evaluate the validity and reliability of the Turkish version of SMIS. Materials and Methods: A cross-sectional validation study with a prospective test–retest component was conducted among 60 patients with anal incontinence at 2 tertiary hospitals in Istanbul, Türkiye. The original SMIS was translated into Turkish and back-translated according to international translation guidelines. Content and construct validity were assessed by experts’ review and factor analysis. Reliability was evaluated using internal consistency (Cronbach’s alpha) and test–retest reliability. Results: As a result of the evaluations made in line with the opinions of the experts in the “continence field,” it has been shown that Turkish SMIS (T-SMIS) serves to measure anal incontinence with its content questions and is stated as valid. Reliability analyses indicated adequate internal consistency (Cronbach’s α = 0.76) and high test–retest reliability (intraclass correlation coefficient; r= 0.72- 0.87, P = .01-.65). Conclusion: The T-SMIS is a psychometrically sound instrument for assessing fecal incontinence severity. Its adaptation into Turkish facilitates standardized clinical evaluation and international comparability. Notably, during the work, an Italian validation was published, highlighting the global applicability of SMIS across different cultures (Clinical trial registration: NCT05755763). Cite this article as: Ersoy Ö, Temel YE. Validity and reliability of the Turkish St. Mark’s Incontinence Score. Turk J Gastroenterol. Published online February 19, 2026. doi: 10.5152/tjg.2026.25551.